Kashmiri refugees at the verge of hepatitis B and C epidemic in the State of Azad Jammu and Kashmir, Pakistan - Syed Ayaz Kazmi; Abdul Rauf; Farheen Shafique; Noreen Asim; Nuzhat shafi; Mahreen Ul Hassan (Universidade de São Paulo, 2022)
ABSTRACT OBJECTIVE To determine the seroprevalence of hepatitis B and C among immigrants residing refugee camps in Muzaffarabad, Azad Kashmir, Pakistan, and to identify possible risk factors for hepatitis B virus (HBV) and hepatitis C virus (HCV) transmission. METHODS Around 1,225 individuals inhabiting Muzaffarabad refugee camps, participated in the study. A qualitative Immuno-Chromatographic Technique was used for initial screening and PCR test was used for detection of HBV and HCV in participants. The major risk factors for HBV and HCV transmission were assessed using a questionnaire approach. RESULTS Around 86 (7.0%) individuals were observed for hepatitis B surface antigen (HBsAg) presence, and 215 (17.5%) individuals were found positive for Anti-HCV. Only 32 (2.6%) individuals were confirmed for HBV DNA and 126 (10.3%) individuals were positive for HCV RNA after PCR. Demographically, both HBsAg and Anti-HCV were found more prevalent in female (4.4% HBsAg and 10.8% Anti-HCV) population as compared to male (2.6% HBsAg and 6.7% Anti-HCV) population. Surprisingly, the HBsAg (23.5%) and Anti-HCV (41.1%) appeared to be more frequent in the age group 62-75 years. Previous history of hepatitis in the family (p < 0.0001), blood transfusion (p = 0.0197) dental treatment (p < 0.0001) and tattooing or piercing on any part of the body (p = 0.0028) were assessed as significant risk factors in HBV and HCV transmission. CONCLUSIONS Presence of 7.0% HBsAg and 17.5% Anti-HCV in a small fragment of the migrant population cannot be overlooked. Lack of awareness among people and negligence of health department could escalate the situation.